2009
DOI: 10.1143/jjap.48.085002
|View full text |Cite
|
Sign up to set email alerts
|

Study of the Electronic Structure of Individual Free-Standing Germanium Nanodots Using Spectroscopic Scanning Capacitance Microscopy

Abstract: High spatial resolution spectroscopic scanning capacitance microscopy (SCM) measurements at room temperature based on the differential capacitance (d C=d V ) versus probe tip-to-substrate bias characteristics, is directly used to characterize the electronic structure of a pyramidal and an ellipsoidal shaped germanium (Ge) nanodot (with physical sizes smaller than the Bohr exciton radius of Ge), among the arrays of Ge nanodots fabricated on a highly doped silicon substrate using an anodic alumina membrane as an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(14 citation statements)
references
References 49 publications
(88 reference statements)
0
14
0
Order By: Relevance
“…Their calculations designate that LNMO (001), LNMO (110), LCMO (001), and LCMO (110) should be ferromagnetic halfmetal, while LNMO (111) and LCMO (111) are ferromagnetic semiconductors with a Coulomb-enhanced band gap and a Hubbard U gap, respectively. Although the electronic structure of the compounds are readily accessible from first principles calculations, however with the advancement in experimental techniques [22,23], the electronic structure of semiconductors could also be obtained experimentally [24,25]. Shuhui Lv et al [26] calculated the electronic structure of the multifunctional La 2 CoMnO 6 at equilibrium and under strain.…”
Section: Introductionmentioning
confidence: 99%
“…Their calculations designate that LNMO (001), LNMO (110), LCMO (001), and LCMO (110) should be ferromagnetic halfmetal, while LNMO (111) and LCMO (111) are ferromagnetic semiconductors with a Coulomb-enhanced band gap and a Hubbard U gap, respectively. Although the electronic structure of the compounds are readily accessible from first principles calculations, however with the advancement in experimental techniques [22,23], the electronic structure of semiconductors could also be obtained experimentally [24,25]. Shuhui Lv et al [26] calculated the electronic structure of the multifunctional La 2 CoMnO 6 at equilibrium and under strain.…”
Section: Introductionmentioning
confidence: 99%
“…Recent researches in the field of materials science [50][51][52] have demonstrated that density functional theory (DFT) provides the best means for predicting solid state properties of materials close to experimental observations [53]. In this study, we use DFT based on the all-electron FPÀ LAPWþlo method, as implemented in the WIEN2K package [54], to investigate the structural, electronic and magnetic properties of Vanadium doped BeS and BeTe with concentration (x¼ 0, 0.25, 0.50, 0.75 and 1.0).…”
Section: Methods Of Calculationsmentioning
confidence: 99%
“…Recently a large number of experimental studies related to the electronic structure [12][13][14], magnetism and magnetic transitions in several Ge-Te based alloys, such as Ge-Cr-Te, Ge-Mn-Te and Ge-Fe-Te have been reported [15][16][17]. In addition, there is a substantial amount of work on the DMS in general (please refer to Ref.…”
Section: Introductionmentioning
confidence: 99%